Unique genetic profile of sporadic colorectal cancer liver metastasis versus primary tumors as defined by high-density single-nucleotide polymorphism arrays - Muñoz-Bellvis, Luís; Fontanillo, Celia; González-González, María; Garcia, Eva; Iglesias, Manuel; Esteban, Carmen; Gutierrez, M L; Abad, M M; Bengoechea, Oscar; De Las Rivas, Javier; Orfao, Alberto; Sayagués, J M (Modern pathology, 2012)
Most genetic studies in colorectal carcinomas have focused on those abnormalities that are acquired by primary tumors, particularly in the transition from adenoma to carcinoma, whereas few studies have compared the genetic abnormalities of primary versus paired metastatic samples. In this study, we used high-density 500K single-nucleotide polymorphism arrays to map the overall genetic changes present in liver metastases ( n =20) from untreated colorectal carcinoma patients studied at diagnosis versus their paired primary tumors ( n =20). MLH1, MSH2 and MSH6 gene expression was measured in parallel by immunohistochemistry. Overall, metastatic tumors systematically contained those genetic abnormalities observed in the primary tumor sample from the same subject. However, liver metastases from many cases (up to 8 out of 20) showed acquisition of genetic aberrations that were not found in their paired primary tumors. These new metastatic aberrations mainly consisted of (1) an increased frequency of genetic lesions of chromosomes that have been associated with metastatic colorectal carcinoma (1p, 7p, 8q, 13q, 17p, 18q, 20q) and, more interestingly, (2) acquisition of new chromosomal abnormalities (eg, losses of chromosomes 4 and 10q and gains of chromosomes 5p and 6p). These genetic changes acquired by metastatic tumors may be associated with either the metastatic process and/or adaption of metastatic cells to the liver microenvironment. Further studies in larger series of patients are necessary to dissect the specific role of each of the altered genes and chromosomal regions in the metastatic spread of colorectal tumors.